High Data Rate Wireless Data Communication - Wang, Dong (My University, 2008)
High data rate (HDR) wireless communication has become one of the global largest business projects recently. Less than 15 years ago, the peak data rate which could be achieved by commercial mobiles was less than 15 kbps. Nowadays, it is possible to achieve more than 14Mbps. This means that the mobile downlink data rate has been improved by about 1000 times during less than two decades only. However, there are many different technologies and standards in the literature. The standards and proposals are changing and modified in very fast manner. Some standards are updated several times per year. In this M.Sc. report we go through some of the most famous HDR technologies such as HSPA, WiMAX, IEEE 802.11n, IEEE 802.20, and IEEE 802.22. The ability to achieve this HDR over wireless channels which are very dynamic and unpredictable comes from the efficient utilization of many new concepts and algorithms. Some of these concepts are the efficient multiple access methods (e.g. OFDM, OFDMA, CDMA, etc.), Adaptive Modulation and Coding (AMC), Multi-Input-Multi-Output (MIMO) antennas, and generally the cross-layer optimization. We introduce many of these concepts in order to make clear comparison between the different HDR solutions, the main contribution of this thesis is the gathering of vast information of very recent HDR techniques. Many of these technologies are still under standardization (however, some commercial products have been already released).
Keywords: high data rate; wireless; fi=Tietoliikennetekniikka|en=Telecommunications Engineering|